The environmental and evolutionary history of Lake Ohrid (FYROM/Albania): interim results from the SCOPSCO deep drilling project - Wagner, Bernd; Koutsodendris, Andreas (Biogeosciences, 2017)
This study reviews and synthesises existing information generated within the SCOPSCO (Scientific Collaboration on Past Speciation Conditions in Lake Ohrid) deep drilling project. The four main aims of the project are to infer (i) the age and origin of Lake Ohrid (Former Yugoslav Republic of Macedonia/Republic of Albania), (ii) its regional seismotectonic history, (iii) volcanic activity and climate change in the central northern Mediterranean region, and (iv) the influence of major geological events on the evolution of its endemic species. The Ohrid basin formed by transtension during the Miocene, opened during the Pliocene and Pleistocene, and the lake established de novo in the still relatively narrow valley between 1.9 and 1.3Ma. The lake history is recorded in a 584m long sediment sequence, which was recovered within the framework of the International Continental Scientific Drilling Program (ICDP) from the central part (DEEP site) of the lake in spring 2013. To date, 54 tephra and cryptotephra horizons have been found in the upper 460m of this sequence. Tephrochronology and tuning biogeochemical proxy data to orbital parameters revealed that the upper 247.8m represent the last 637kyr. The multi-proxy data set covering these 637kyr indicates long-term variability. Some proxies show a change from generally cooler and wetter to drier and warmer glacial and interglacial periods around 300ka. Short-term environmental change caused, for example, by tephra deposition or the climatic impact of millennial-scale Dansgaard-Oeschger and Heinrich events are superimposed on the long-term trends. Evolutionary studies on the extant fauna indicate that Lake Ohrid was not a refugial area for regional freshwater animals. This differs from the surrounding catchment, where the mountainous setting with relatively high water availability provided a refuge for temperate and montane trees during the relatively cold and dry glacial periods. Although Lake Ohrid experienced significant environmental change over the last 637kyr, preliminary molecular data from extant microgastropod species do not indicate significant changes in diversification rate during this period. The reasons for this constant rate remain largely unknown, but a possible lack of environmentally induced extinction events in Lake Ohrid and/or the high resilience of the ecosystems may have played a role.